Echology of crytocoryne auriculata engler in Pakan, Sibu, Sarawak - Jaerah, bt. Mohidin. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The ecological study of Cryptocoryne auriculata was conducted at Sg. Gamalat and S~. Tajuk, Pakan, Sibu, Sarawak. The total number of plant at Sg. Gamalat was 72 plants/0.5m and 50 plants/O.5m2 at Sg. Tajuk Dry weight ratio for leaf, petiole and root were not significantly differed between the two locations. Total dry weight, dry weight for leaf, petiole and root, leaf area ratio and specific leaf area were significantly differed between Sg. Gamalat and Sg. Tajuk. There was a total 107 trees from 37 species were recorded from five plots in area with in the presence of C. auriculata. The five most dominant species were Shorea macrophylla (IV= 29.57). Duriozibethinus (lV=18.66), Saraca declinata (rv= 18.27), Shorea seminis (lV= 15.53) and Nephelium lappaceum (rv= 13.56). The total above ground biomass was 133.72 tonlha. Shorea macrophylla had the highest biomass (17.93 tonlha) while Desmos dasymaschala had the lowest biomass (0.04 tonlha). Stomatal index were higher at Sg. Tajuk compare at Sg. Gamalat. Soil analysis at Sg. Tajuk showed that pH value was 5.5 and nitrogen content was 0.1 %. Total organic carbon was 1.04% and calcium has the higher ion exchange. Sand (fine) was the higher percentage (58.52%) compare with sand-coarse (32.64%), silt (5.20%) and clay (3.64%).